Implementation Of Geostrategy – Geoecology – Geocultural In Accelerate Blue Economic Development Of Fakfak Regency - Jumadi Jumadi; Angky Soedrijanto; Sri Rahayu; Untung Tamsil (Research Trend in Technology and Management, 2024)
The research aims to determine strategies for implementing geostrategy-geoecological-geocultural-based development for efforts to accelerate regional blue economy development in Fakfak regency. Descriptive research using a semi-qualitative approach, carried out in coastal areas and small islands. Data was obtained from the conversion of in-depth interview results using weighting techniques. Respondents are coastal communities, small islands, and parties who make policies. The research results show that developing a blue economy must begin with improving community culture through a geocultural approach, and building downstream marine fisheries businesses and building renewable energy sources to take advantage of geoecological advantages.